Critical analysis of contemporary clinical research in muscle‐invasive and metastatic urothelial cancer. Issue 11 (1st March 2013) - Galsky, Matthew D.; Hendricks, Ryan; Svatek, Robert; Bangs, Rick; Hoffman‐Censits, Jean; Clement, Jessica; Dreicer, Robert; Guancial, Elizabeth; Hahn, Noah; Lerner, Seth P.; O'Donnell, Peter H.; Quale, Diane Zipursky; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND There have been no improvements in the treatment of metastatic urothelial cancer in the past several decades. A census of contemporary clinical research in this disease was performed to identify potential barriers and opportunities. METHODS These authors performed a search for clinical trials exploring interventions in muscle‐invasive and metastatic urothelial cancer, using the ClinicalTrials.gov registry. Data extracted from the registry included title, recruitment status, interventions, sponsor, phase, enrollment, study design, and study sites. RESULTS Among 120 eligible trials exploring interventions in muscle‐invasive and metastatic urothelial cancer, 73% were phase 2 and 73% were nonrandomized. The majority (63%) involved treatment in the metastatic disease state. The median planned enrollment size per trial was 45 patients (interquartile range, 47 patients). The majority of trials (55%) involved ≤ 3 study sites. Trials most commonly explored interventions in the first‐line metastatic (30%) or second‐line metastatic (37%) settings. Targeted therapeutics were studied in 58% of the trials. Among 56 trials that completed enrollment, the median time to complete accrual was 50 months (range, 10‐109 months), and these trials enrolled a median of 40 patients per trial (interquartile range, 44 patients). CONCLUSIONS The majority of contemporary clinical trials in muscle‐invasive and metastatic urothelial cancer are small, nonrandomized, phase 2 trials involving 1 to 3 study sites. Enhanced communication and collaboration among the urothelial cancer community, and other stakeholders, is needed to facilitate the design and conduct of trials capable of expediting progress in this disease. Cancer 2013;119:1994–1998. © 2013 American Cancer Society.